Health risk assessment of heavy metals on workers at the Doura Oil Refinery, Baghdad - Abd Al-Ameer, Afyaa S.; Abdullah, Enaam J. (Iraqi Journal of Science, 2025)
Pollutants resulting from oil refining operations cause harmful effects on public health, especially for workers exposed for long periods. Measuring the level of specific contaminants in the blood of refinery workers is necessary to understand the relationship between exposure to pollutants and health status. This study aims to determine the levels and nature of heavy metals in the blood of occupational exposure workers in the Al-Dora refinery, Baghdad. A total of 20 blood samples (15 exposed workers and 5 non-exposed individuals (control)) were investigated to assess the level of heavy metals. An atomic absorption spectrometer (AAS) was used to measure the levels of Cr, Cd, Pb, and V in the blood samples. The mean concentrations of heavy metals in the blood of the exposed group are significantly higher compared to the control groups, with Cr at 65.27 μg/dl, Cd at 163.93 μg/dl, Pb at 37.33 μg/dl, and V at 153.33 μg/dl. The results showed a significant difference between the exposed and control groups (p<0.001), which indicates a strong correlation between heavy metal levels in the blood and exposure status. There was also a correlation between the level of heavy metals in the blood of exposure groups, age, smoking, and duration of work. In particular, workers aged 15 years and more, smoking workers, and female workers had higher levels of heavy metals. Moreover, Cd and V levels exceeded permissible limits. Our findings highlight the importance of implementing comprehensive health and safety protocols to reduce the risk factors associated with age, smoking, and prolonged exposure among workers in oil refineries to improve workers' overall health and well-being.